Integrated Disease Management for Vegetable Crops in Florida - Tim Momol; Jim Marois; Ken Pernezny; Steve Olson (EDIS)
This document is Fact Sheet PP111, one of a series of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published November 2001.